Emotional Suppression and Oneiric Expression in Psychosomatic Disorders: Early Manifestations in Emerging Adulthood and Young Patients - Settineri, Salvatore; Frisone, Fabio; Alibrandi, Angela; Merlo, Emanuele Maria (Frontiers in Psychology, 2019)
Background: the function of emotions, beginning from the proto-emotions, is the adaptation to the environment. This is based on the Homeorhesis, the equilibrium due to the adaptive operation of excitement and the dissipation of emotions. The object relations of the participants foresee the practice of defense mechanisms in a continuum that goes from the consciousness to the oneiric activities. The predominant and maladaptive use of defense mechanisms in the psychosomatic phenomenology, can be identified with deficits in emotional awareness, with the impossibility to manage excitement and dissipation of emotions foreseen by the oneiric phenomena. Method: the observation group is composed by 140 participants, 56 males (43 %) and 84 females (57%),with pathological-functional disorders of psychosomatic domain. The study had been conducted with the use of measures related to the conscious defense of suppression (Suppression Mental Questionnaire), to the emotional awareness linked to the psychosomatic phenomena (Diagnostic Criteria for Psychosomatic Research Structured Interview-DCPR-SI) and to the states of perturbation and conservation of oneiric activities (The Manheim Dream Questionnaire-MADRE). Results: Significant inverse correlations emerged among rationalization, repressive function and illness Denial, as for the suppression mental questionnaire factors and irritable mood, but for Regression in the service of the Ego; inverse and significant correlations emerged among suppression, repressive function, rationalization and gastrointestinal psychosomatic outcomes and among suppression, repression and cardiological psychosomatic outcomes. Regarding alexithymia, a positive correlation emerged with rationalization and inverse with Regression in the service of the Ego. Positive correlations emerged between illness denial and overall emotional tone, for disease phobia and meaningfulness and for cardiological psychosomatic outcomes and nightmare distress and recurring nightmares. Conclusions: the study of such outcomes due to a prevalent defensive style based on suppression, suggest the identification of a key phenomenon, which translates into maladjustment that goes from functional disorders to parasomnia. The bridge established by the obfuscation of conscious contents until the manifestations of disturbance of ancient activities such as oneiric ones, expresses the need to transform an emotional maladaptive style, in line with classic literature and the current state of art.